2002
DOI: 10.1037/0894-4105.16.4.548
|View full text |Cite
|
Sign up to set email alerts
|

Interactions of focal cortical lesions with error processing: Evidence from event-related brain potentials.

Abstract: Electrophysiological and hemodynamic studies have suggested that structures in the vicinity of the anterior cingulate cortex are involved in performance monitoring, particularly in detection of errors. Bidirectional interactions between the frontomedian system involved in performance monitoring and the lateral prefrontal cortex as well as the orbitofrontal cortex have been proposed, but few studies have directly addressed this issue. The authors used a speeded flankers task to investigate error-related event-r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

13
73
0

Year Published

2004
2004
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 84 publications
(86 citation statements)
references
References 57 publications
13
73
0
Order By: Relevance
“…The ERN is supposed to be the main electrophysiological "output signal" of this performancemonitoring network. Indeed, it has been shown that lesion damage to many of the regions found in our conjunction analysis severely attenuate or fully diminish the ERN (Ullsperger et al, 2002;Stemmer et al, 2004;Seifert et al, 2011), and the same is true for the white-matter tracts connecting these areas (Hogan et al, 2006). Similar effects could be predicted for the novelty-N2.…”
Section: Discussionsupporting
confidence: 62%
“…The ERN is supposed to be the main electrophysiological "output signal" of this performancemonitoring network. Indeed, it has been shown that lesion damage to many of the regions found in our conjunction analysis severely attenuate or fully diminish the ERN (Ullsperger et al, 2002;Stemmer et al, 2004;Seifert et al, 2011), and the same is true for the white-matter tracts connecting these areas (Hogan et al, 2006). Similar effects could be predicted for the novelty-N2.…”
Section: Discussionsupporting
confidence: 62%
“…Thus, at least in some tasks pMFC seems to be more directly linked to adjustment processes in stimulus-encoding areas than DLPFC. It has been suggested that lateral prefrontal areas maintain task-representations (Gehring and Knight, 2000;Ullsperger et al, 2002;Ullsperger and von Cramon, 2006) that are strengthened after conflict or errors (Botvinick et al, 2001). Although pMFC and DLPFC activations occur in close temporal proximity, there might be several intermediate neuronal steps between monitoring in pMFC and the updating of task-representations in DLPFC.…”
Section: Discussionmentioning
confidence: 99%
“…Physiologically, error detection is accompanied by skin conductance responses and changes in heart rate (Hajcak et al, 2003(Hajcak et al, , 2004, and both ACC and (especially) the insula are implicated in such responses (Kuniecki et al, 2003), as well as in cortisol and energy (glucose) regulation (Allport et al, 2004;Christensen et al, 2004;Ottowitz et al, 2004) and errorrelated processes (Menon et al, 2001). Additionally, both ACC and insula have a necessary role in the normal occurrence of the ERN (Ullsperger et al, 2002;Ullsperger and Cramon, in press) and are implicated by neuroimaging studies in depersonalization (Lanius et al, 2005;Phillips et al, 2001) and in risk-avoidance and punishment in relation to neuroticism (Paulus et al, 2003). Interestingly, administration of the anxiolytic benzodiazepine lorazepam has been related to decreased cortisol mobilization (Collomp et al, 1994;Hellhammer et al, 1988), decreased ERN amplitude (De Bruijn et al, 2004) and decreased insula activity (Paulus et al, 2005).…”
Section: Discussionmentioning
confidence: 99%